(untitled) (Advances in Military Technology, 2022)
The paper is focused on a method of experimental black powder burning law finding. This method issues from records acquired during black powder charge burning tests in closed vessel (ballistic bomb). Evaluation of data sets brings courses of parameters needed for calculation of instantaneous values of black powder burning rate. The burning law is then given as spare regression function of experimental data.